2007
DOI: 10.1590/s1677-54492007000400012
|View full text |Cite
|
Sign up to set email alerts
|

Profilaxia antimicrobiana em cirurgia vascular periférica: cefalosporina ainda é o padrão-ouro?

Abstract: Nas cirurgias vasculares periféricas, as cefalosporinas têm seu uso consagrado como agente antimicrobiano profilático de escolha. Recentemente, observamos uma mudança nos padrões de colonização, prevalência de patógenos e suscetibilidade geral aos antimicrobianos. Os patógenos multirresistentes vêm se tornando cada vez mais freqüentes nas infecções de ferida cirúrgica vascular, demonstrando variações regionais e locais quanto à suscetibilidade aos antimicrobianos profiláticos utilizados na rotina cirúrgica. Os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
1
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
1
1
1
4
Order By: Relevance
“…8 Lichtenfels et al showed incidences of 1.5-2.9% for clean wounds, 2.8-7.7% for clean and clean-contaminated, 6.4-15.2% for contaminated, and 7.1-40% for dirty wounds. 42 Similar figures were also described by others. 5,43,44 Likewise, we found a progressively higher incidence of SSI from clean to dirty wound procedures.…”
Section: Discussionsupporting
confidence: 81%
“…8 Lichtenfels et al showed incidences of 1.5-2.9% for clean wounds, 2.8-7.7% for clean and clean-contaminated, 6.4-15.2% for contaminated, and 7.1-40% for dirty wounds. 42 Similar figures were also described by others. 5,43,44 Likewise, we found a progressively higher incidence of SSI from clean to dirty wound procedures.…”
Section: Discussionsupporting
confidence: 81%
“…The infection rate was high, compared to other studies 20 , despite the sharp use of prophylactic antibiotics. This proves that the antibiotic must be associated with a set of measures to minimize the occurrence of infection.…”
Section: Discussion Discussion Discussion Discussion Discussioncontrasting
confidence: 58%
“…Oliveira et al (2005) encontraram um perfil elevado de resistência à tetraciclina, concordando com os resultados encontrados no hospital humano, no qual todas as bacté-rias isoladas foram resistentes à tetraciclina, com exceção de Pseudomonas. Lichtenfels et al (2007) obtiveram alta resistência a ampicilina, ciprofloxacina, clindamicina e gentamicina. No hospital veterinário, a bactéria Staphylococcus apresentou resistência a todos os antimicrobianos testados, exceto a amoxacilina/ácido clavulânico.…”
Section: Discussionunclassified